EFFECT OF CYTOKININ ANALOGUES ON CYTOKININ METABOLISM AND STRESS RESPONSIVE GENES UNDER OSMOTIC STRESS IN WHEAT - SHIVANI NAGAR; AJAY ARORA; V. P. SINGH; S. RAMAKRISHNAN; DEEPIKA K. UMESH; SHAILESH KUMAR; RAVI P. SAINI (The Bioscan, 2015)
Osmotic stress induced by conditions like drought, salinity and heat etc. impairs plant growth and development by affecting plant physiological processes. Present study was conducted in laboratory to understand the role cytokinin analogues (TDZ and BAP) in osmotic stress amelioration and their relative efficiency in inducing stress tolerance. Twenty days old wheat seedlings were treated 20% PEG-6000 to induce osmotic stress (-0.491 MPa). Exogenous application of cytokinin analogues enhanced endogenous cytokinin levels by up-regulating expression of IPT (isopentenyl transferase) and down-regulating CKX (cytokinin oxidase) gene expression under osmotic stress. Further, increase in relative water content (30%), membrane stability (15%) and nitrogen assimilation was observed along with delayed leaf senescence in cytokinin treated seedlings under osmotic stress. The current finding suggested that application of TDZ was found to be more effective as compared to BAP even at lower concentrations.